2015
DOI: 10.4067/s0717-95022015000300039
|View full text |Cite
|
Sign up to set email alerts
|

Histological Validation of Morphochromatically-Defined Gonadal Maturation Stages of Green Abalone (Haliotis fulgens) Philippi,1845 and Pink Abalone (Haliotis corrugata) Wood, 1828

Abstract: SUMMARY:Identifying the maturity stage of specimens is essential for the determination of the spawning season, which in turn facilitates the formulation of adequate fisheries management measures for the sustainable use of sea resources, such as abalone. This study aims to validate, based on histological evidence, a gonad maturation scale that encompasses four morphochromatically-defined stages (developing, maturity, spawning and resting) for females and males, plus an additional stage for reproductively inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Twelve-month hybrid abalones were obtained from the grading station in ZhongXin Yongfeng (Fuzhou, China) in early April 2022. Studies have shown the color of male and female abalone gonads was milky white and grayish green, respectively (Shepherd and Laws, 1974;Vélez-Arellano et al, 2015). Abalones were acclimated and fed a commercial diet for two weeks in the sh steak of abalone farm in Lianjiang Country, Fujian Province before the experiment.…”
Section: Animals and Culture Conditionsmentioning
confidence: 99%
“…Twelve-month hybrid abalones were obtained from the grading station in ZhongXin Yongfeng (Fuzhou, China) in early April 2022. Studies have shown the color of male and female abalone gonads was milky white and grayish green, respectively (Shepherd and Laws, 1974;Vélez-Arellano et al, 2015). Abalones were acclimated and fed a commercial diet for two weeks in the sh steak of abalone farm in Lianjiang Country, Fujian Province before the experiment.…”
Section: Animals and Culture Conditionsmentioning
confidence: 99%